2013
DOI: 10.1371/journal.pone.0078362
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Malaria on Households and the Health System in Enugu State Southeast Nigeria

Abstract: BackgroundMalaria is the number one public health problem in Nigeria, responsible for about 30% of deaths in under-fives and 25% of deaths in infants and 11% maternal mortality. This study estimated the economic burden of malaria in Nigeria using the cost of illness approach.MethodsA cross-sectional study was undertaken in two malaria holo-endemic communities in Nigeria, involving both community and hospital based surveys. A random sample of 500 households was interviewed using interviewer administered questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(108 citation statements)
references
References 15 publications
6
97
1
4
Order By: Relevance
“…Allium sativum supplemented along with artesunate low dose and high dose treated animals also showed non-significant decrease in SDH at all time intervals ( Table 2, Table 4). [32][33][34] Artemisinin displays the most rapid action among the current drugs against Plasmodium falciparum as well as Plasmodium vivax induced malaria. 35 Further, Artemisinin and its derivatives have been observed to exhibit potency against the asexual and erythrocytic forms of P. falciparum and P. vivax.…”
Section: Resultsmentioning
confidence: 99%
“…Allium sativum supplemented along with artesunate low dose and high dose treated animals also showed non-significant decrease in SDH at all time intervals ( Table 2, Table 4). [32][33][34] Artemisinin displays the most rapid action among the current drugs against Plasmodium falciparum as well as Plasmodium vivax induced malaria. 35 Further, Artemisinin and its derivatives have been observed to exhibit potency against the asexual and erythrocytic forms of P. falciparum and P. vivax.…”
Section: Resultsmentioning
confidence: 99%
“…The populations at risk are citizens of Anambra State and, like most parts of Nigeria, the impact of malaria has posed a huge public health concern [2] Ethnically, the people of Anambra State are Igbo and are mainly Christians with a few traditional worshipers [10]. Their enterprising business acumen has earned them the reputation as skilled business people.…”
Section: Population At Riskmentioning
confidence: 99%
“…The economic burden of malaria is the subject of much debate at both international, regional and local level [10][11][12][13][14]. Calculating the loss of productivity resulting from malaria related sickness is a pre requisite necessary to estimate the economic burden of malaria [15].…”
Section: Introductionmentioning
confidence: 99%
“…Calculating the loss of productivity resulting from malaria related sickness is a pre requisite necessary to estimate the economic burden of malaria [15]. In some part of Nigeria, studies showed that the direct and indirect costs due to malaria burden was estimated to exceeded US $2 billion10 whereas, in some other places, households spend between $2 to $25 and $20 to $15 respectively on malaria treatment and prevention each month [8,12]. However, there is scarcity of this information in Bayelsa state.…”
Section: Introductionmentioning
confidence: 99%